AMINO ACID DEPRIVATION THERAPY: A PROMISING AVENUE IN CANCER TREATMENT - E, Bindu; Thampi, B S Harikumaran; Antony, Robert (International Journal of Pharma and Bio Sciences, 2026)
A promising method for treating cancer is amino acid deprivation therapy, which targets the metabolic reliance of cancer cells on particular amino acids. Because of their elevated rates of proliferation and dysregulated metabolic pathways, many cancer cells have a higher need for certain amino acids than normal cells. The therapeutic potential of amino acid deprivation is examined in this paper, with particular attention paid to the depletion of essential amino acids that are essential for the survival and proliferation of cancer cells, such as glutamine, methionine, and arginine. There is discussion of several tactics, such as the use of small-molecule inhibitors, dietary restrictions, and recombinant enzymes (such as arginine deiminase and asparaginase).The study also assesses preclinical and clinical research that shows these methods are safe and effective for various cancer types. Additionally examined are the mechanisms by which amino acid deficiency triggers cell cycle arrest, autophagy, and apoptosis. Potential combinatorial techniques to improve therapeutic efficacy are discussed, along with difficulties relating to toxicity and resistance mechanisms. Future directions in amino acid deprivation therapy are highlighted in the review's conclusion, with a focus on the necessity of individualized strategies catered to each tumors unique metabolic weakness.